Experimental Study on The Effect of Arches Setting on Semi-Flexible Monocrystalline Solar Panels - Arissetyadhi, Iwan; Dewi, Tresna; Kusumanto, RD (Universitas Muhammadiyah Malang, 2020)
Indonesia has a high potential for renewable energy, especially solar power, due to its location in the equator and blessed with an abundance of sunlight. However, the energy potential from the sun is not maximally utilized. One of the efforts to increase the generated electricity and efficiency is by applied the panels in arches setting. This setting is made possible by the availability of the semi-flexible monocrystalline solar panel. This paper investigates the increment of harvested power and efficiency by arranging the solar panel in concave, convex, and plane settings. The data were taken in August 2019, where Palembang experiences the dry season and January 2020 during the rainy season. The highest power produced (20.27 Watt) and efficiency (13.14%) were achieved in a concave setting during the dry season. The convex setting produced more power and efficiency (13.26 Watt and 9.30%) compared to the plane setting (10.24 Watt and 9.71%). These results show that arches setting are more efficient to harvest solar power and give more extensive applications such as to power a dynamics mobile robot applied in agriculture.